Selective cytotoxicity of Gomortega keule essential oil through a ROS-mediated pro-apoptotic mechanism - Madrid, Alejandro; Silva, Valentina; Russo, Alessandra; Moller, Alejandra Catalina; Sánchez, Elizabeth; Villena, Joan; Jara-Gutiérrez, Carlos; Montenegro, Iván (Frontiers in Pharmacology, 2025)
Cancer is a leading cause of mortality worldwide, prioritizing the search for new therapies with improved toxicity profiles. Natural products, such as essential oils (EOs), are a valuable source of potential chemotherapeutic agents. Gomortega keule, a Chilean endemic tree, has traditional uses, but its cytotoxic potential remains unexplored. This study investigated the chemical composition and cytotoxic activity of Gomortega keule leaf EO. The chemical analysis revealed a unique profile rich in diterpenes (>50%), mainly phyllocladene (28.08%) and kaur-16-ene (19.74%), suggesting a distinct chemotype. The EO demonstrated potent cytotoxic activity against breast (MCF-7), prostate (PC-3), and colon (HT-29) cancer cell lines, with IC50 values of 3.97, 2.43, and 9.76 μg/mL, respectively. Remarkably, the EO exhibited exceptional selectivity, proving significantly more toxic to cancer cells than to non-tumorigenic cells. Specifically, it achieved a Selectivity Index (SI) of 24.01 for breast cancer cells compared to normal MCF-10A cells. Crucially, this selectivity profile significantly outperformed standard chemotherapeutic agents (daunorubicin and 5-fluorouracil), which displayed high toxicity towards healthy cells in this model. The mechanism of action involves the selective induction of reactive oxygen species (ROS), leading to mitochondrial membrane depolarization (ΔΨm) and caspase activation, culminating in apoptotic cell death. These findings highlight G. keule EO as a promising source for developing selective cytotoxic agents.